Host protein ARF1 is a proviral factor for SARS-CoV-2 and a candidate broad-spectrum therapeutic target - Cunhuan Zhang; Yuan-Qin Min; Heng Xue; Haiyan Zhang; Kunpeng Liu; Yichao Tian; Ziying Yang; Zihan Zhao; Hang Yang; Chao Shan; Xiulian Sun; Yun-Jia Ning (Nature Communications)
Abstract SARS-CoV-2 and its emerging variants pose continuing threats to public health. SARS-CoV-2 assembles at the ER–Golgi intermediate compartment (ERGIC), where the viral membrane (M) protein highly accumulates to act as the central driver. However, how M is concentrated in the ERGIC, which hosts factor(s), may be involved, and whether they could be exploited as broad-spectrum antiviral targets remains unclear. Here, we identify an M-interacting host protein, ARF1, as a proviral factor that bolsters the propagation of SARS-CoV-2 and its variants in cultured cells and the viral infection and pathogenicity in female K18-hACE2 mice. By its N-terminal helix, ARF1 interacts with M and facilitates M’s ERGIC accumulation and thus M-driven virion production. Consistently, pharmacological ARF1 inhibition by small molecules disrupts both ARF1 and M concentration at the ERGIC, blocking virion assembly and propagation. Furthermore, a designed peptide mimicking the M-targeted motif of ARF1 competitively blocks M-ARF1 interaction, M accumulation at the ERGIC, and viral assembly and propagation in vitro. Moreover, the peptidomimetic inhibitor exhibits therapeutic efficacy against SARS-CoV-2 infection and pathogenicity in vivo. These findings provide critical insights into the basic biology of SARS-CoV-2 and demonstrate the potential to develop pan-SARS-CoV-2 therapeutics by targeting ARF1 and/or the ARF1-M interaction interface.